P023 Evaluation of Beta-D-glucan assay as a tool for antifungal stewardship at a hospital in Mumbai, India. (20th September 2022) - Thakkar, Pooja; Singhal, Tanu; Shah, Sweta; Jadhav, Shweta
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM: Objectives: Clinical evidence suggests that the Beta-D glucan (BDG) test is useful as a tool for antifungal stewardship by helping in discontinuing empiric antifungal therapy. This study was hence initiated with the following objectives: (1) to calculate the percentage of echinocandin prescriptions in patients with a subsequent negative BDG test and the compliance to recommendations for stopping echinocandins for the above prescriptions, (2) to study outcomes in patients where echinocandins were stopped, and (3) to study the total cost savings. Methods: The study was conducted for a 1-year period from January 2021 to December 2021 in a tertiary care hospital in Mumbai. The antimicrobial stewardship committee recommends sending a serum sample for BDG along with paired blood culture for all patients before starting empirical antifungal therapy. The choice of empiric antifungal therapy at our hospital is echinocandins (caspofungin, micafungin, and anidulafungin). The BDG test was performed using Fungitell® assay (Associates of Cape Cod, Massachusetts) that quantitatively measures 1, 3-β-D-glucan levels which is run twice a week on Wednesday and Saturday. The cut-offs for a negative, indeterminate and positive result are 60 pg/ml, 60-79 pg/ml, and >80 pg/ml respectively. The result of the BDG test and blood culture was promptly informed to the consultant in charge and recommendations were made to discontinue the echinocandin if both tests were negative. The compliance with these recommendations was monitored. The patients in whom the echinocandin was stopped were monitored during their hospital stay or on day 28 after stopping the echinocandin whichever was earlier. The total cost savings [in Indian Rupees (INR) and converted into US Dollars (USD)] were calculated based on an average of 10 days extra therapy with echinocandins. Results: A total of 337 echinocandins were prescribed in 294 patients and reviewed during the study period; anidulafungin (170, 50%) was the most commonly prescribed echinocandin followed by caspofungin (131, 39%), and micafungin (36, 11%). The BDG result as well as blood fungal cultures were negative for 53 prescriptions in 49 patients (15.7%). The compliance to recommendations for stopping echinocandin in these prescriptions was 100% (53/53). None of these 49 patients had a sterile culture positive for Candida during the follow-up period. A total of 17 patients died, 1 was discharged against medical advice, 19 were discharged and 12 were still in hospital at the end of the follow-up period. No deaths could be attributed to invasive fungal infections at 28-day follow-up. Total cost savings were 6794 440 INR, corresponding to 89 000 USD during the study year. Conclusion: BDG test-based stewardship strategy helped in reducing the use of echinocandins with cost savings and no increased risk of invasive fungal infections related to adverse outcomes in patients where echinocandins were discontinued. The universal compliance to recommendations to deescalate could be achieved by constant dialogue between the departments of Clinical Microbiology and Clinical Medicine.